NEW HYBRID F1 OF WHITE HEAD CABBAGE FROM SYNGENTA - A. Balabanova (Овощи России)
Syngenta has been for many years in Russian agricultural market, and presented annually new hybrids and cultivars of vegetable crops, as well as plant protection means against pathogens and pests. This year we have released new hybrids of white head cabbage that have well passed all field trials and have been approved in practice under different conditions. These are ‘Jatodor F1’, ‘Bolikor F1’, ‘Storidor F1’, ‘Elastor F1’ and ‘Lexicon F1’.